(NaNTIBIOTIKI GRUPPY AMINOGLIKOZIDOW (B/s - (NnAWA[IN(B, (NsERGEJ mIHAJLOWI^s; (NfOMINA(B, (NiNESSA pETROWNAs; (NsAZYKIN(B, (N`RIJ oSIPOWI^s ((NmOSKWA (B:s (NmEDICINA(B,s, 1977)
(NrEZ(B.: (NANGL(B.s
(NsPISOK LIT(B.: (NS(B. 200-204s
Keywords: (NaNTIBIOTIKI AMINOGLIKOZIDNYEs; (NmOLEKULQRNAQ BIOLOGIQs; (NgENETIKA MIKROBIOLOGI^ESKAQs; (NbIOHIMIQs